2020
DOI: 10.1038/s41598-020-75158-7
|View full text |Cite
|
Sign up to set email alerts
|

Major discrepancy between factual antibiotic resistance and consumption in South of France: analysis of 539,037 bacterial strains

Abstract: The burden of antibiotic resistance is currently estimated by mathematical modeling, without real count of resistance to key antibiotics. Here we report the real rate of resistance to key antibiotics in bacteria isolated from humans during a 5 years period in a large area in southeast in France. We conducted a retrospective study on antibiotic susceptibility of 539,107 clinical strains isolated from hospital and private laboratories in south of France area from January 2014 to January 2019. The resistance rate… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…Moreover, Pseudomonas' carbapenem resistance had a mean rate of 30.3% ± 3.3% and 33% ± 7.7% for IPM and MEM, respectively, consistent with previous studies [16]. Interestingly, Pseudomonas' carbapenem resistance was unaffected by the decrease in consumption of IPM, which is in line with the findings of other studies [16][17][18]. Although some studies report a correlation between hospital resistance of PAE and carbapenem consumption levels [19], our results echo the findings of Álvarez-Marín et al (2021) showing that the correlation between carbapenem consumption and incidence density of carbapenem-resistant Pseudomonas Aeruginosa is minimal [20].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, Pseudomonas' carbapenem resistance had a mean rate of 30.3% ± 3.3% and 33% ± 7.7% for IPM and MEM, respectively, consistent with previous studies [16]. Interestingly, Pseudomonas' carbapenem resistance was unaffected by the decrease in consumption of IPM, which is in line with the findings of other studies [16][17][18]. Although some studies report a correlation between hospital resistance of PAE and carbapenem consumption levels [19], our results echo the findings of Álvarez-Marín et al (2021) showing that the correlation between carbapenem consumption and incidence density of carbapenem-resistant Pseudomonas Aeruginosa is minimal [20].…”
Section: Discussionsupporting
confidence: 92%
“…[26]. Similarly, Gianella et al conducted a research in the region of Emilia-Romagna, Italy, and identified higher numbers of DTR patterns, representing 11% of all isolates, with K. pneumoniae accounting for all but one strains [23], while reports from France [27], Hungary [28] or United States [10] highlighted a much lower prevalence of DTR, constantly reported as maximum 1%. Interestingly, there is a wide spectrum of DTR variance among bacterial species, the highest shares of DTR being found among UTIs caused by A. baumannii [10].…”
Section: Discussionmentioning
confidence: 96%
“…As for E. faecium , we distinguish between vancomycin-resistant (VREfm) and vancomycin-susceptible. We also calculated the isolate density of difficult to treat (DTR) organisms as previously described [ 28 , 29 , 30 ]. This implies resistance to carbapenems, beta-lactams, fluoroquinolones, and additional antimicrobials where applicable (i.e., piperacillin-tazobactam, aztreonam in Pae and Ab; vancomycin, linezolid in Sau and Efm).…”
Section: Methodsmentioning
confidence: 99%